Gender Inequality in the Enforcement of Criminal Law: A Case Study of Sexual Violence Victims in Indonesia - Septiawan, Rendi; Isyri, Neria Fatihatul; Failasufa, Juana (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
Gender inequality in criminal law enforcement remains a persistent problem in Indonesia, particularly in cases involving sexual violence. Although legal reforms such as the Law on Sexual Violence Crimes (UU TPKS) aim to protect victims and uphold justice, many women survivors continue to face obstacles in the justice system. This study aims to examine the structural and cultural barriers that hinder fair and gender-sensitive legal processes for victims of sexual violence. A qualitative method was elawmployed, using in-depth semi-structured interviews and document analysis with survivors, police officers, and prosecutors across five provinces: West Kalimantan, Central Kalimantan, South Sulawesi, Central Java, and East Nusa Tenggara. The core finding of the study is that gender bias and institutional inadequacy consistently undermine the realization of justice for victims. law enforcement officers often lack adequate gender-based training and hold discriminatory attitudes toward victims. Survivors frequently experience secondary victimization, such as victim-blaming and revictimization during legal proceedings, which discourages them from pursuing justice. Structural limitations, such as insufficient personnel, poor inter-agency coordination, and influence from powerful perpetrators, also contribute to case withdrawals and legal stagnation. This study highlights a significant gap between normative legal frameworks and their practical implementation. The novelty of this research lies in its empirical exploration of both victim experiences and institutional challenges in law enforcement. The study contributes to gender and legal scholarship by offering insights for reforming criminal justice practices. It recommends institutional training, victim-centered procedures, and stronger enforcement of gender-sensitive legal standards. In conclusion, achieving justice for sexual violence victims requires systemic change that prioritizes survivor dignity, agency, and legal protection.